PREVENTIVE CONSERVATION: A CONCEPT SUITED TO THE CONSERVATION OF EARTHEN-ARCHITECTURAL HERITAGE? - Joffroy, Thierry (Memorias del Seminario Iberoamericano de Arquitectura y Construcción con Tierra - SIACOT, 2012)
The concept of preventive conservation (PC) is relatively old, as the term was already in use as early as the end of the 19th century. As the deinition implies, the theory of preventive conservation was developed mainly in the context of work on movable heritage. Yet the concept appears to be equally applicable to built heritage, and more speciically to earthen-architectural heritage whose basic raw material is usually fragile by nature and in some circumstances, can decay relatively fast. Though earthen architecture is varied, one of its characteristics is that for each typology, there is always a speciic way of ensuring durability or minimizing the risk of damage. This is achieved by implementing a variety of measures that depend on the physical, economic and social context of the site. What is interesting is that all of these measures are aimed at protecting and extending the life expectancy of the structures in question, thus linking them to the concept of preventive conservation. This leads to the conclusion that preventive conservation is by its very nature a concept well adapted to earthen structures. Taking into account climate change, which brings about unusual situations, reinforces the suitability of the concept, which allows us to anticipate natural disaster. This paper examines the suitability and limits of applying the concept of PC in the conservation of earthen architecture through theoretical analysis and practical examples. It concludes with recommendations for its adoption, taking into account intrinsic speciicities, and both the tangible and intangible values of the heritage being considered for conservation.